Análise dos níveis de homocisteína e ácido fólico em modelo de carcinogênese para validação como biomarcadores para rastreio de câncer gástrico - COSTA, Joana de Fátima Ferreira Borges da (2023)
The evolution of gastric carcinogenesis is still poorly known. For this work we used the model of gastric carcinogenesis in Cebus apella, a non-human primate from the New World. We treated six animals with N-methyl-nitrosourea (MNU). During the studies, clinical, hematological and biochemical analyzes were performed, including C-reactive protein, folic acid and homocysteine. All animals developed pre-neoplastic lesions and five (05) of them died of drug intoxication before the development of neoplasia. The last surviving animal from MNU treatment developed intestinal-type gastric adenocarcinoma, seen through endoscopy on the 940th day. The levels of C-reactive protein and the concentration of homocysteine increased and the level of folic acid experienced with the presence of disturbances in the animals treated with MNU. The hematological and biochemical results corroborate the observations found in patients with gastric cancer, proving that Cebus apella are interesting in vivo models to study this neoplasm. Thus, we conclude that homocysteine and folic acid levels are altered according to the stage of carcinogenesis, but we could observe that homocysteine increases as the tumor is established, in evolution, folic acid levels decrease with tumor progression. Corroborating with studies that show that homocysteine and folic acid levels are inversely provided and that they are bichemical parameters sensitive to the development of cancer and that thus can be used as biochemical markers for tracking carcinogenic development.